The effect of the KATP channel on energy metabolism in skeletal muscle during fatigue - Benkhalti, Maria (University of Ottawa (Canada), 2009)
KATP channels are found on the sarcolemma where they affect muscle contractility and thus, energy demand. They are also found in the mitochondria where they affect ATP production. The overall objective was to determine how the KATP channel affects skeletal muscle metabolism during fatigue, elicited with one tetanic contraction every sec for 3 min. Exposing Kir6.2-/- flexor digitorum brevis (FDB) muscles, which have no sarcolemmal KATP channels, to the KATP channel blocker, glibenclamide, or the opener, pinacidil, did not affect lactate production during the three min fatigue. However, DMSO, used to dissolve glibenclamide and pinacidil caused a decrease in lactate content during the last two min of fatigue, an effect not observed in its absence of DMSO. It is therefore possible that DMSO also influence how glibenclamide and pinacidil affect lactate content during the last two minutes of fatigue. Further studies were then restricted to a comparison between wild type and Kir6.2-/- FDB. The amount of glucosyl units entering glycolysis, from glycogen breakdown and glucose uptake, was the same between wild type and Kir6.2 -/- FDB, while lactate production was much less in Kir6.2-/- FDB following fatigue. It is suggested that the absence of K ATP channel activity in Kir6.2-/- FDB results in an increased oxidative capacity in which more pyruvate enters the Krebs cycle than in wild type FDB. This suggestion is supported by the fact that the oxygen uptake is greater in Kir6.2-/- than wild type mice during a 24 hour period.
Keywords: Biology, Molecular.; Biology, Genetics.; Biology, Cell.